Card and board game design for medical education: length and complexity considerations - Cosimini, Michael Joseph; Collins, Jolene (Korean journal of medical education, 2023)
Purpose: There is growing use of games for health professions education. Card and board games are relatively easy to develop, effective for education, supported by educational theory, and generally well accepted by learners; yet, they remain relatively infrequently described in the medical education literature.Methods: A questionnaire was developed to understand barriers to use of card and board games and to understand user preferences to inform their development. The questionnaire was offered to students and educators downloading a printable antibiotic card game online.Results: The questionnaire was completed by 335 health professionals primarily by physicians, pharmacists, and their trainees. Participants described preferences for shorter games and games with lower complexity. Player counts in the two to four range were the most commonly desired. The most frequently cited barriers were lack of availability in desired subjects, cost, and concerns about content accuracy.Conclusion: Educators looking to develop or use serious card and board games should start with shorter, lower-complexity games. Methods to assure and demonstrate content accuracy for educational games should be explored by educators and researchers.